Colombia's accession to the OECD and its effect on public policy (2014)
This document provides an opinion regarding the process of accession of Colombia to the OECD, is written in the tradition of the academic mainstream of public policy , the above into consideration the success in the accession process will impact the way that the country produces, implements and maintains its administration policies addressing a multidisciplinary field due to the need to meet legislative requirements, social, economic, cultural, sociological, infrastructure and communication between other types to provide welfare to its citizens.